IMPROVING THE STUDENTS’ INTEREST IN WRITING DESCRIPTIVE TEXT USING BUBBLE MAP OF THE SEVENTH GRADE STUDENTS OF SMP IT HIDAYATUL MUBTADIIN DEMAK - Dwi Janarko (Universitas PGRI Semarang, 2014)
The main objectives of this research are: (1) to describe how the teacher apply Bubble Map as media in teaching decriptive text; (2) to know the students’ interest in learning descriptive text before being taught by using Bubble Map; (3) to know the students’ interest in learning descriptive text after being taught by using Bubble Map as media. This study is qualitative research. The population of the research is the seventh grade students of SMP IT Hidayatul Mubtadiin Demak in the academic year 2013/2014. 30 students of the seventh grade is the population and the sample. In the first meeting, the students were taught descriptive text without by using Bubble Map as the media. In the second meeting, the students were taught descriptive text by using Bubble Map as the media.The instruments to take the data are observation sheet, questionnaire, and interview. From the observation sheet, the data shows that students became more active in class when taught using Bubble Map. The transcript during the learning activity dialogue proves the data. The questionnaire was given to the students. The questionnaire results 93.3% students are interested in studying descriptive text by using Bubble Map. The interview was asked to the teacher. It results that the teacher knows that their students involved active more in studying descriptive text by using Bubble Map